Identification and expression analysis of chalcone synthase and dihydroflavonol 4-reductase in Clivia miniata - Viljoen, Christopher D.; Snyman, Marius C.; Spies, Johan J. (South African journal of botany, 2013)
Clivia miniata is a popular breeding variety. The production of anthocyanin has been studied in Clivia species and the presence of key genes in anthocyanin production, chalcone synthase (CHS) and dihydroflavonol 4-reductase (DFR) confirmed. However, it is currently unknown to what extent these genes are expressed in different flower tissue during flower development. Thus the aim of this study was to determine the expression of CHS and DFR in C. miniata var. miniata, an orange flowered variety, and C. miniata var. citrina, a yellow flowered variety, in tepal, carpel and stamen at flower developmental stage two to six. As expected, the anthocyanin content in orange flowers was higher than that of yellow flowers. The expression of CHS and DFR correlated to anthocyanin content. Anthocyanin gene expression and production was found primarily in the tepal. There was a high correlation between CHS and DFR expression suggesting that these genes are subject to coordinate regulation in C. miniata. •CHS &DFR expression was higher in orange than in yellow flowers.•Anthocyanin content was similar to CHS and DFR expression.•Data suggests that these genes are key in pigment production in C. miniata.•CHS &DFR appear to have coordinate regulation.